Pedicled distal phalanx fillet flap for finger length preservation in trauma. Issue 4 (April 2016) - Salibi, Andrej; McArdle, Ciarstan; Morritt, Andrew N.
Summary: Lawnmower injuries to the digits are becoming increasingly common and are often complex in nature with multiple levels of injury. The management of these injuries as with that of other hand injuries is often tailored to the individual patient considering factors such as occupation and hobbies with the ultimate goal of restoration of function and a sensate fingertip. The concept of using amputated, mangled or non-salvageable parts in a form of fillet flap has become more common in the recent years. We report a complex case of a multi-level injury to the dominant index finger of a professional typist from a lawnmower where finger length was maximised using a pedicled distal phalanx fillet flap which ultimately allowed the patient to return to work.